Optical properties of zinc borotellurite glass system doped with erbium and erbium nanoparticles for photonic applications - Abd Azis, Muhammad Noorazlan; Mohamed Kamari, Halimah; El-Mallawany, Raouf A. H.; Mohd Fudzi, Faznny; Chua, Ee Von (Springer, 2017)
Comparative analysis on optical properties between two glass series (a—ordinary glass, b—glass with nanoparticles) have been estimated. The two glass series (a—ordinary glass, b—glass with nanoparticles) with compositions {[(TeO2)0.70 (B2O3)0.30]0.70 (ZnO)0.30}1−y (Er2O3/Er2O3 nanoparticles)y; y = 0.005, 0.01, 0.02, 0.03, 0.04, 0.05 mol% were successfully prepared by using melt-quenching method. The TEM, EDX and XRD have been used to confirm the existence of nanoparticles and all elements in the glass system. The density of b—glass with nanoparticles are found greater than a—ordinary glass. The optical properties of the glass series were characterized by using Ellipsometer and UV–Vis spectrophotometer. There is a linear increasing trend in refractive index of the glass series along with concentration of erbium and erbium nanoparticles oxide. The refractive index of b—glass with nanoparticles is greater than a—ordinary glass. Moreover, the absorption peaks of a—ordinary glass are more intense than b—glass with nanoparticles. The glass with nanoparticles will offer a potential materials for nanophotonic devices.